The professor's guide to taming technology : leveraging digital media, Web 2.0, and more for learning - King, Kathleen P.; Cox, Thomas D. (Emerald Publishing Limited : Information Age Publishing, 2011)
This book is provided as a guide, encouragement and handbook for faculty to introduce digital media in language you can understand and provide strategies and activities you can quickly assimilate into your teaching. We are excited that more people will be able to benefit from the powerful help and guidance contained in this book. We are even more exhilarated as we anticipate how each of you will discover applications and new directions we would never anticipate, and look forward. We look forward to your innovations as you use the material you discover here.This book responds to the needs of our changing world and students by revealing innovative technology applications and how faculty are and can use digital media in teaching in higher education because faculty make the quickest changes and learn how to do it best. It is a valuable resource for faculty from faculty, because it allows the sharing of successful teaching experiences with digital media with our worldwide colleagues so they may modify it, extend it, and improve it.Moreover, in our work with faculty across all disciplines, we also find that many struggle to think about teaching in ways in which they can incorporate technology meaningfully. While we might be experts in our discipline (chemistry, philosophy, music, etc) due to the curriculum of terminal degrees, we might not have strong preparation in instructional design.We have been fortunate to bring together faculty experts across different disciplines to specifically speak about how and why to use digital media in higher education settings. We realize we are asking you to think about your way of teaching with new ideas and strategies. Therefore, we try to illustrate them with clear examples. These different approaches include clear descriptions of what these activities look like, why to develop and implement them, and how to do so for your specific needs.
Keywords: Education, Higher -- Computer-assisted instruction.; Educational technology.; Digital media.; Web 2.0.; Education -- Computers & Technology.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books